Physical Interaction of Human T-Cell Leukemia Virus Type 1 Tax with Cyclin-Dependent Kinase 4 Stimulates the Phosphorylation of Retinoblastoma Protein - Haller, Kerstin (American Society for Microbiology, 2002)
The Tax oncoprotein of human T-cell leukemia virus type 1 (HTLV-1) induces leukemia in transgenic mice and permanent T-cell growth in vitro. In transformed lymphocytes, it acts as an essential growth factor. Tax stimulates the cell cycle in the G(1) phase by activating the cyclin-dependent kinase (CDK) CDK4 and CDK6 holoenzyme complexes. Here we show that Tax directly interacts with CDK4. This binding to CDK4 was specific, since Tax did not bind to either CDK2 or CDK1. The interaction with CDK4/cyclin D complexes was observed in vitro, in transfected fibroblasts, in HTLV-1-infected T cells, and in adult T-cell leukemia-derived cultures. Binding studies with several point and deletion mutants indicated that the N terminus of Tax mediates the interaction with CDK4. The Tax/CDK complex represented an active holoenzyme which capably phosphorylates the Rb protein in vitro and is resistant to repression by the inhibitor p21(CIP). Binding-deficient Tax mutants failed to activate CDK4, indicating that direct association with Tax is required for enhanced kinase activity. Tax also increased the association of CDK4 with its positive cyclin regulatory subunit. Thus, protein-protein contact between Tax and the components of the cyclin D/CDK complexes provides a further mechanistic explanation for the mitogenic and immortalizing effects of this HTLV-1 oncoprotein.